2016
DOI: 10.1038/cddis.2016.145
|View full text |Cite
|
Sign up to set email alerts
|

Role of long non-coding RNA-RNCR3 in atherosclerosis-related vascular dysfunction

Abstract: Atherosclerosis is one of the most common vascular disorders. Endothelial cell (EC) dysfunction and vascular smooth muscle cell (VSMC) proliferation contributes to the development of atherosclerosis. Long non-coding RNAs (lncRNAs) have been implicated in several biological processes and human diseases. Here we show that lncRNA-RNCR3 is expressed in ECs and VSMCs. RNCR3 expression is significantly upregulated in mouse and human aortic atherosclerotic lesions, and cultured ECs and VSMCs upon ox-LDL treatment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
151
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(154 citation statements)
references
References 44 publications
2
151
1
Order By: Relevance
“…The screen also identified MeCP2-associated RNA including MALAT1, a long ncRNA implicated in regulating blood vessel growth (30,31), as well as RNCR3, which is thought to be atheroprotective (32). MeCP2 coexists in distinct complexes that support a functional role in RNA processing and transcriptional suppression (33).…”
Section: Discussionmentioning
confidence: 99%
“…The screen also identified MeCP2-associated RNA including MALAT1, a long ncRNA implicated in regulating blood vessel growth (30,31), as well as RNCR3, which is thought to be atheroprotective (32). MeCP2 coexists in distinct complexes that support a functional role in RNA processing and transcriptional suppression (33).…”
Section: Discussionmentioning
confidence: 99%
“…The level of RNCR3 was up‐regulated in aortic atherosclerotic lesions, and the knockdown of RNCR3 decreased the proliferation of ECs and VSMCs in the thoracic aorta. The overexpression of miR‐185‐5p reduced the expression of RNCR3, and silencing miR‐185‐5p potentiated the viability and proliferation of HUVECs, while this effect was partially reversed by RNCR3 knockdown . Krüppel‐like factor 2 (KLF2) was a target of miR‐185‐5p that was also regulated by RNCR3.…”
Section: Mirna Acting As a Negative Regulator Of Lncrnas To Prevent Tmentioning
confidence: 99%
“…The level of RNCR3 was up-regulated in aortic atherosclerotic lesions, and the potentiated the viability and proliferation of HUVECs, while this effect was partially reversed by RNCR3 knockdown. 57 Krüppel-like factor 2 (KLF2) was a target of miR-185-5p that was also regulated by RNCR3. Down-regulated RNCR3 reduced the KLF2 level and suppressed the viability and proliferation of HUVECs, whereas the overexpression of KLF2 eliminated these functions.…”
Section: Regulator Of Lncrnas To Pre Vent Th E Proliferation and Migrmentioning
confidence: 99%
“…11 Intervention of lncRNA-RNCR3 is reported as a promising strategy for treatment of atherosclerosis. 12 lncRNA activated by tumor growth factor β (lncRNA-ATB), located on chromosome 14, is aberrantly expressed in numerous malignancies and contributes to proliferation, migration, and invasion in cancer cells. 13 Previous studies have shown that tumor growth factor-β (TGF-β) is implicated in angiogenesis, and lncRNA-ATB can be upregulated by TGF-β.…”
Section: Introductionmentioning
confidence: 99%